A supported sub-nano iridium oxide cluster material, and a preparation method and application thereof
Patent Information
- Application Number
- CN202611078030.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-09-29
AI Technical Summary
本发明的第三个目的在于提供一种基于上述载体负载型亚纳米氧化铱团簇材料制备的质子交换膜电解水制氢阳极催化剂,该催化剂通过将亚纳米IrOx团簇均匀分散于载体表面,在有效降低Ir载量的同时显著提升其OER催化活性,增加活性位点数目,提高贵金属利用率,不仅克服了现有技术中IrOx阳极催化剂贵金属原子利用率低、催化活性与稳定性欠佳的问题,且有效解决了传统催化剂在PEMWE中载量高、活性差的问题,可拓展其在电催化析氧领域的应用
[0020]本发明所述负载型亚纳米氧化铱团簇材料,以金属氧化物作为载体材料,其表面负载有均匀分散的亚纳米氧化铱团簇(IrO2或IrOx),利用金属氧化物与Ir前驱体之间的强相互作用,在高温氧化过程中有效限域了IrOx颗粒的生长,实现了亚纳米IrOx在载体表面的高度均匀分散。一方面,亚纳米IrOx提供了丰富的催化活性位点,显著提升了催化剂的OER活性;另一方面,载体与活性组分间的相互作用有效抑制了IrOx在运行过程中的团聚和溶出,显著提升了催化剂的运行稳定性。
Smart Images

Figure CN122833647A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional catalyst technology, specifically relating to a supported sub-nanometer iridium oxide cluster material, and further disclosing its preparation method and its use in preparing a proton exchange membrane electrolysis water electrolysis hydrogen production anode catalyst. Background Technology
[0002] Hydrogen energy, as a clean and efficient secondary energy source, possesses significant advantages such as high energy density, flexible storage and transportation, and zero carbon emissions, making it a crucial carrier for building a future low-carbon energy system and ensuring energy security. Proton exchange membrane electrolysis (PEMWE) technology, with its high energy conversion efficiency, high hydrogen purity, fast dynamic response, flexible start-up and shutdown, and good compatibility with fluctuating renewable energy sources, has become one of the core technological routes for large-scale, low-cost, and efficient green hydrogen production. Among these, the extreme oxygen evolution reaction (OER) involves multi-step four-electron transfer and O-O bond formation. Its kinetics are slow, the reaction energy barrier is high, and the overpotential is large, requiring highly active catalysts for efficient operation. The activity of the catalyst is a key factor limiting the OER reaction.
[0003] Currently, iridium (Ir)-based catalysts have become the mainstream anode catalysts for PEMWE due to their excellent activity and durability under strong acid and high oxidation potential conditions (E.-J. Kim, J. Shin, J. Bak, et al., Stabilizing role of Mo in TiO2-MoO). x (Supported Ir catalyst toward oxygenevolution reaction, Appl. Catal. B: Environ. Energy, 280 (2021) 119433.). Due to the scarcity of Ir reserves in the Earth's crust and the limited global supply, its market price has remained high for a long time, directly leading to a significant increase in the cost of core materials for electrolyzers, severely restricting the development of PEMWE technology towards large-scale, low-cost commercialization. Therefore, how to reduce the loading of the precious metal Ir in the anode catalyst layer and improve atom utilization and catalytic efficiency while ensuring catalytic activity and stability has become a research hotspot and core technological challenge in the field of PEMWE.
[0004] In recent years, using metal oxides as supports to load Ir particles or clusters to reduce the amount of precious Ir required has been an effective way to improve the utilization rate of precious metals. In this type of catalyst, the support can not only disperse the active Ir components and reduce agglomeration, but also potentially regulate the electronic structure of Ir through metal-support interaction (SMSI), thereby optimizing catalytic performance. For example, Darius Hoffmeister et al. used TiO2 supports to support IrO2 catalysts. By selecting TiO2 with a low specific surface area to form a thicker IrO2 shell, they achieved a low Ir loading of only 0.1 mg. Ir cm -2 At that time, in 2A cm -2 The overpotential at the current density was reduced by 43 mV compared to commercial catalysts, achieving a significant deloading effect (D. Hoffmeister, S. Finger, R. Pokhrel, et al., Structural optimization of TiO2 supported IrO2 catalyst for proton exchange membrane water electrolysis, Chem. Eng. J., 517 (2025) 164281.).
[0005] However, although using metal oxide supports to support Ir-based catalysts is an effective way to reduce the amount of precious metals used, existing technologies still have key drawbacks. Currently reported supported Ir-based catalysts generally have Ir particle sizes in the range of 1-5 nm. For example, Qin et al. used an interface engineering strategy to improve the oxygen evolution reaction performance of low-Ir supported catalysts using a highly conductive Ti4O7 support. Although their Ir particle size reached approximately 1.57 nm, a high overpotential still existed in PEMWE (Y. Qin, Y. Wang, R. Wen, et al., Interface-engineering strategy for boosting low-Ir catalytic water oxidation using a conductive Ti4O7 support, ACS Catal., 14 (2024) 13915-13926).
[0006] Studies have shown that further reducing the particle size of IrO2 to the sub-nanometer level (<1 nm) can significantly improve the number of active sites and the utilization rate of noble metals (X. Cao, H. Cheng, R. Gui, et al., Sub-nano Ir-based alloyclusters by hierarchical confinement effect for water splitting, Angew. Chem. Int. Ed., 64 (2025) e202509993). However, how to make sub-nano IrO2 particles smaller remains a challenge. x Achieving controllable loading of clusters remains a significant technical challenge. Existing methods for preparing sub-nanometer clusters generally suffer from cumbersome synthetic steps, demanding reaction conditions, and low product yields, enabling only small-scale, milligram-level preparations in the laboratory and failing to meet the practical requirements for large-scale production (W.Wang, Z. Zhang, B. Chu, et al., Subnanometric iridium clusters atomicallyenrooted on non-stoichiometric tungsten oxides for boosting acidic oxygenevolution reaction, Adv. Funct. Mater., 36 (2026) e20812.). Furthermore, due to the limitations of sub-nanometer IrO... x Due to its high surface energy, IrO is highly susceptible to migration and aggregation during preparation, drying, high-temperature oxidation, and PEMWE operation, leading to activity degradation. Currently, there is a lack of effective anchoring strategies to balance sub-nanometer size and long-term stability. Therefore, the field anticipates the development of sub-nanometer IrO. x Catalyst preparation technology that features uniformly dispersed clusters, simple preparation process, and easy industrial scale-up, while also possessing excellent catalytic activity and electrochemical stability, is the core key to breaking through the current technical bottleneck of PEMWE anode catalysts and promoting their low-cost commercial application. Summary of the Invention
[0007] The first objective of this invention is to provide a carrier-supported sub-nanometer iridium oxide cluster material, which can achieve the loading of sub-nanometer iridium oxide clusters; The second objective of this invention is to provide a method for preparing the above-mentioned carrier-supported sub-nanometer iridium oxide cluster material, especially a scalable preparation method. This method effectively achieves long-term stable loading of sub-nanometer iridium oxide clusters through carrier treatment, and the process is simple and easy to scale up. The third objective of this invention is to provide a proton exchange membrane anode catalyst for hydrogen production via water electrolysis, prepared based on the aforementioned supported sub-nanometer iridium oxide cluster material. This catalyst utilizes sub-nanometer IrO... x The clusters are uniformly dispersed on the support surface, effectively reducing Ir loading while significantly improving its OER catalytic activity, increasing the number of active sites, and improving the utilization rate of precious metals. This not only overcomes the limitations of existing IrO... x The anode catalyst suffers from low utilization of precious metal atoms, poor catalytic activity and stability, and effectively solves the problems of high loading and poor activity of traditional catalysts in PEMWE, which can expand its application in the field of electrocatalytic oxygen evolution.
[0008] To address the aforementioned technical problems, this invention provides a supported sub-nanometer iridium oxide cluster material, the material comprising a support and supported active clusters; wherein, The active clusters include sub-nanometer iridium oxide clusters with a particle size of <1 nm; The carrier comprises metal oxides.
[0009] Specifically, in the supported sub-nanometer iridium oxide cluster material, the active clusters are loaded with 30-70 wt% based on the support.
[0010] Specifically, the supported sub-nanometer iridium oxide cluster material: The iridium oxide cluster includes Ir x O y Where x=1, y=1.5-2.2; and / or, The metal oxide includes one or a mixture of several of niobium pentoxide, chromium dioxide, titanium dioxide, zirconium dioxide, or tin dioxide.
[0011] It should be noted that the metal oxide support described in this invention includes, but is not limited to, niobium pentoxide, chromium dioxide, titanium dioxide, zirconium dioxide, tin dioxide, etc., as long as it can remain stable in an acidic oxidizing environment and interact with the Ir precursor to confine sub-nanometer IrO. x The growth of clusters can achieve the purpose of this invention.
[0012] This invention also discloses a method for preparing the supported sub-nanometer iridium oxide cluster material as described above, comprising the following steps: (1) Take a selected amount of the metal oxide for surface pretreatment to obtain the desired carrier, and add a dispersing solvent to mix and form a carrier suspension; (2) Continue to add alkali metal nitrate and Ir source material to the carrier suspension, mix and disperse to obtain a mixed liquid; (3) The mixture is evaporated to dryness to obtain a precursor solid; the precursor solid is then subjected to high-temperature calcination to obtain the desired supported sub-nanometer iridium oxide cluster material.
[0013] Specifically, in the preparation method of the supported sub-nanometer iridium oxide cluster material, the pretreatment step in step (1) includes grinding and sieving the metal oxide to obtain the carrier powder, and performing Ar / O2 plasma low-temperature treatment and / or acid washing on the carrier powder. The grinding steps include a step of coarse grinding with an agate mortar for 5-30 minutes; and / or a step of ball milling with a planetary ball mill at a speed of 300-600 rpm for 0.5-6 hours. The sieving step yields a carrier powder of 200-400 mesh; and / or, In the plasma cryogenic treatment step, the volume ratio of Ar gas to O2 is (5-20):1; and / or, The duration of the plasma cryogenic treatment step is 5-60 minutes; and / or, The temperature of the plasma cryogenic treatment step is 50-300℃; and / or, The acid used in the pickling step includes at least one of nitric acid, hydrochloric acid, and sulfuric acid; and / or, The acid concentration used in the pickling step is 0.1-2 mol / L; and / or, The pickling temperature in the pickling step is 25-80℃; and / or, The pickling time for the pickling step is 0.5-6 hours; and / or, The dispersing solvent includes one or more of the following: alcohol solvents or water; for example, methanol, ethanol, isopropanol, etc.; and / or, The carrier suspension has a carrier solids content of 0.01-0.05 wt%.
[0014] Specifically, in the preparation method of the supported sub-nanometer iridium oxide cluster material, step (2) includes: The alkali metal nitrates include one or a mixture of several of sodium nitrate, potassium nitrate, zinc nitrate, etc.; and / or, The Ir source material includes one or a mixture of several of iridium chloroiridic acid, iridium trichloride, potassium iridium chloroiridate, or iridium acetylacetonate; and / or, The amount of the alkali metal nitrate added is 1-15 times the mass of the carrier; and / or, The mass ratio of the carrier to the Ir source material is 10:1 to 1:10; and / or, The dispersion process includes one or more of the following methods: ultrasonication, stirring, or ball milling; and / or, It also includes the step of adding a surfactant to the mixture, preferably, the surfactant comprising one or a mixture of several of hexadecyltrimethylbromoalkane, polyvinylpyrrolidone, and sodium dodecyl sulfate.
[0015] Specifically, in the preparation method of the supported sub-nanometer iridium oxide cluster material, step (3) includes: The temperature of the evaporation step is 40-65℃; and / or, The evaporation step takes 20-150 minutes; and / or, The atmosphere for the high-temperature calcination step is an oxygen-containing atmosphere, preferably an air atmosphere; and / or, The temperature of the high-temperature calcination step is 300-550℃; and / or, The heating rate of the high-temperature calcination step is 5-10℃ / min; and / or, The high-temperature calcination step takes 30-180 minutes; and / or, The method also includes the steps of collecting the high-temperature calcination product for dispersion, washing, separation and drying; for example, the collected product is ultrasonically dispersed in water, then washed to remove impurities such as alkali metal nitrates, and dried to obtain the material.
[0016] Preferably, the dispersion includes ultrasonic dispersion, and the processing time is preferably 10-60 min; Preferably, the washing includes vacuum filtration washing, centrifugal washing, or dialysis washing; for example, vacuum filtration washing uses 0.5-5.0L of water per 1g of product; or centrifugal washing requires a rotation speed of 6000-12000rpm; or dialysis washing requires a dialysis bag pore size of 0.5-50nm and a dialysis time of 3-10 days. Preferably, the drying process includes drying in a blower-type drying oven at a temperature preferably 40-60°C.
[0017] The present invention also discloses the use of the supported sub-nanometer iridium oxide cluster material as described above for preparing anode catalysts for proton exchange membrane water electrolysis to produce hydrogen.
[0018] The present invention also discloses a proton exchange membrane electrolysis anode catalyst for hydrogen production, comprising the supported sub-nanometer iridium oxide cluster material.
[0019] The present invention also discloses a proton exchange membrane electrolysis water production hydrogen production process, including the step of anodic catalysis using the proton exchange membrane electrolysis water production hydrogen production anode catalyst.
[0020] The supported sub-nanometer iridium oxide cluster material of this invention uses a metal oxide as a carrier material, and its surface is loaded with uniformly dispersed sub-nanometer iridium oxide clusters (IrO2 or IrO).x By utilizing the strong interaction between metal oxides and Ir precursors, IrO is effectively confined during high-temperature oxidation. x The growth of particles achieved sub-nanometer IrO x Highly uniform dispersion on the carrier surface. On the one hand, sub-nanometer IrO x It provides abundant catalytic active sites, significantly improving the OER activity of the catalyst; on the other hand, the interaction between the support and the active component effectively inhibits IrO. x Agglomeration and dissolution during operation significantly improve the operational stability of the catalyst.
[0021] The supported sub-nanometer iridium oxide cluster material of the present invention uses a series of pretreatment methods, such as coarse grinding with an agate mortar and a planetary pre-grinding, to effectively break down the existing micron-sized hard agglomerates and obtain 200-400 mesh ultrafine carrier powder by sieving. Furthermore, by combining the Ar / O2 plasma low-temperature treatment process, oxygen vacancies, step sites and lattice defects can be artificially constructed on the carrier surface to avoid Ir multi-site aggregation from the intrinsic structure level of the carrier.
[0022] The supported sub-nanometer iridium oxide cluster material of this invention utilizes a preferred pretreatment method to specifically and efficiently activate the surface of the metal oxide support. From a microscopic perspective, the pretreatment process can regulate the distribution of defect sites and functional groups on the support surface, increasing active anchoring sites, thereby achieving highly dispersed and stable loading of sub-nanometer iridium oxide clusters and inhibiting cluster migration and aggregation. Simultaneously, it strengthens the metal-support interaction, regulates the electronic structure of the iridium oxide clusters, optimizes the adsorption energy of reaction intermediates, and exposes more catalytically active sites, thus more effectively improving its intrinsic activity, cycle stability, and atom utilization as a catalyst, significantly enhancing its application advantages. This method enables stable loading of sub-nanometer iridium oxide clusters, further enhancing its application advantages as a catalyst.
[0023] The supported sub-nanometer iridium oxide cluster material of this invention, through a carrier loading control strategy and pretreatment methods such as plasma activation, can effectively achieve stable loading of iridium oxide clusters, significantly reduce the amount of precious metal Ir used, and effectively alleviate the problem of precious metal resource scarcity; at the same time, it improves catalyst performance and achieves a balance between low cost and high performance.
[0024] The preparation method of the supported sub-nanometer iridium oxide cluster material of the present invention only involves modifying and pretreating the metal oxide support. The preparation method has the advantages of simple process, mild reaction conditions, and easy industrial scale-up, and can achieve kilogram-scale preparation. It provides a practical and feasible technical solution for the large-scale industrial production of efficient, low-cost, and highly stable proton exchange membrane water electrolysis anode catalysts.
[0025] The supported sub-nanometer iridium oxide cluster material described in this invention is used as an anode catalyst for proton exchange membrane water electrolysis. It has both excellent catalytic activity and electrochemical stability. It can not only operate stably in application, but also has an extremely low decay rate. Its application performance is good, effectively breaking through the technical bottleneck of current PEMWE anode catalysts and helping to promote its low-cost commercial application. Attached Figure Description
[0026] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments and accompanying drawings, wherein... Figure 1 The X-ray diffraction pattern of the niobium pentoxide-supported sub-nanometer iridium oxide cluster catalyst prepared in Example 1 of this invention; Figure 2 Transmission electron microscopy (TEM) images of the niobium pentoxide-supported sub-nanometer iridium oxide cluster catalyst prepared in Example 1 of this invention and IrO x Particle size analysis; Figure 3 This is a scanning electron microscope image of the niobium pentoxide-supported sub-nanometer iridium oxide cluster catalyst prepared in Example 1 of the present invention; Figure 4 The scanning electron microscope (SEM) elemental distribution results of the niobium pentoxide-supported sub-nanometer iridium oxide cluster catalyst prepared in Example 1 of this invention; Figure 5 The constant current polarization curve of the niobium pentoxide-supported sub-nanometer iridium oxide clusters prepared in Example 1 of this invention as an anode catalyst in PEMWE; Figure 6 The constant current durability test curve of the niobium pentoxide supported sub-nanometer iridium oxide clusters prepared in Example 1 of the present invention as an anode catalyst in PEMWE; Figure 7 The constant current polarization curve of the niobium pentoxide-supported sub-nanometer iridium oxide clusters prepared in Example 7 of this invention as an anode catalyst in PEMWE; Figure 8 The constant current polarization curve of the niobium pentoxide-supported sub-nanometer iridium oxide clusters prepared in Comparative Example 1 of this invention as an anode catalyst in PEMWE. Figure 9 The constant current polarization curve of the niobium pentoxide-supported sub-nanometer iridium oxide clusters prepared in Comparative Example 2 of this invention as an anode catalyst in PEMWE. Detailed Implementation
[0027] To further understand the present invention, preferred embodiments of the present invention are described below in conjunction with specific implementation methods. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention and not for limiting the claims of the present invention.
[0028] In existing technologies, the iridium-based catalyst at the anode of proton exchange membranes suffers from insufficient exposure of active sites, and small-particle-size IrO... x Addressing the issue of high catalyst activity but poor stability, this invention provides a method for preparing a supported sub-nanometer iridium oxide cluster catalyst and its application in a proton exchange membrane water electrolysis device, belonging to the field of catalyst preparation technology. This invention uniformly loads sub-nanometer iridium oxide clusters onto a metal oxide support, utilizing the confinement and stabilizing effect between the support and the active component. This significantly improves the operational stability while maintaining the high activity of the sub-nanometer iridium oxide clusters and effectively reduces the amount of precious metal Ir used. The prepared metal oxide-supported sub-nanometer iridium oxide cluster catalyst exhibits excellent catalytic activity and stability in the acidic oxygen evolution reaction. The catalyst preparation process is simple and can be used for mass production.
[0029] This invention also discloses a method for preparing the supported sub-nanometer iridium oxide cluster material as described above, comprising the following steps: (1) Take a selected amount of the metal oxide for surface pretreatment to obtain the desired carrier, and add a dispersing solvent to mix and form a carrier suspension; (2) Continue to add alkali metal nitrate and Ir source material to the carrier suspension, mix and disperse to obtain a mixed liquid; (3) The mixture is evaporated to dryness to obtain a precursor solid; the precursor solid is then subjected to high-temperature calcination, washed to remove alkali metal nitrates and dried to obtain the desired supported sub-nanometer iridium oxide cluster material.
[0030] As an exemplary embodiment, the method for preparing the supported sub-nanometer iridium oxide cluster material, which can be used to prepare anode catalysts for proton exchange membrane water electrolysis to produce hydrogen, provided by the present invention, includes the following steps: (1) Carrier pretreatment Metal oxide carriers were selected and subjected to coarse grinding with an agate mortar and pre-grinding with a planetary mill to break up micron-sized hard agglomerates. The resulting ultrafine carrier powder was obtained by sieving. The ultrafine carrier powder was then subjected to low-temperature Ar / O2 plasma treatment to artificially construct oxygen vacancies, step sites, and lattice defects on the carrier surface, thereby preventing Ir multi-site aggregation from the intrinsic structure of the carrier. The obtained ultrafine carrier was then added to a solvent and uniformly dispersed to form a carrier suspension. The metal oxide support is selected from one or more of niobium pentoxide, titanium dioxide, chromium dioxide, tin oxide, and zirconium oxide. The coarse grinding time for the agate mortar is 5-30 minutes; the time for the planetary ball mill is 0.5-6.0 hours, and the rotation speed is 300-600 rpm. The plasma cryogenic treatment time is 5-60 minutes. (2) Precursor stepwise mixing and grinding ultrasonic dispersion First, alkali metal nitrates are added to the suspension. After the alkali metal nitrates are fully adsorbed, noble metal Ir source materials are added so that Ir ions are embedded in the gaps between alkali metal ions to form natural spatial barriers. After the feeding is completed, the system is simultaneously dispersed to finally obtain a uniform and stable mixed solution. Among them, the Ir source materials include one or more of chloroiridium acid, iridium trichloride, potassium chloroiridium, and iridium acetylacetonate; The alkali metal nitrate includes one or more of sodium nitrate, potassium nitrate, zinc nitrate, or ammonium nitrate, and its addition amount is 1-15 times the mass of the metal oxide carrier. The ratio of the metal oxide support to the noble metal Ir source is 10:1 to 1:10. The dispersion process includes one or more methods such as ultrasonication, stirring, and ball milling; for example, ultrasonic dispersion time is 0.5-5.0 h; stirring time is 0.5-5.0 h and rotation speed is 300-650 rpm; ball milling time is 0.5-6.0 h and rotation speed is 300-600 rpm; or grinding is 5-30 min. (3) High-temperature oxidation treatment of molten salt The resulting mixed solution was placed in a rotary evaporator for rotary drying to remove the solvent and obtain a precursor solid. The precursor solid was then placed in air for high-temperature calcination of molten salt, i.e., a high-temperature oxidation process. After the reaction was completed, the product was cooled to room temperature by natural cooling or rapid cooling. The product was then ultrasonically dispersed in water and washed by centrifugation, filtration or dialysis to remove impurities such as molten salt from the system. The washed product was then dried to obtain a small-particle-size iridium oxide catalyst supported on a carrier. The water bath temperature for rotary drying is 40-65℃, and the rotary drying time is 20-150 min. The heating rate of the high-temperature calcination treatment is 5-10℃ / min, the calcination temperature is 300-550℃, and the heat treatment time is 30-180min. The ultrasonic dispersion treatment time for deionized water is 10-60 min; the water addition for filtration washing is 0.5-5.0 L per 1 g of product; the drying temperature of the forced-air drying oven is 40-60℃; or the speed required for centrifugal washing is 6000-12000 rpm; or the dialysis bag pore size required for dialysis washing is 0.5-50 nm, and the dialysis time is 3-10 days.
[0031] All raw materials used in the following examples are analytical grade chemicals and have not undergone further processing.
[0032] Example 1 A large amount of niobium pentoxide support was pre-milled in a planetary ball mill for 40 minutes, and then sieved to obtain 200-mesh ultrafine support powder. The obtained ultrafine support powder was then placed in a plasma reaction chamber, evacuated, and purged with an Ar / O2 mixed gas (volume ratio 10:1). The working pressure was adjusted to 20 Pa, and radio frequency plasma was activated. The mixture was treated at 120°C for 5 minutes, cooled under the atmosphere, and removed to obtain the niobium pentoxide precursor. 0.2 g of the above niobium pentoxide precursor was weighed and placed in a container, and a mixed solvent of 10 mL isopropanol and 10 mL water was added and mixed. The mixture was then ultrasonically dispersed for 30 minutes to form a support suspension.
[0033] First, add 5.0 g of sodium nitrate to the above carrier suspension, and disperse by ultrasonication for 20 min. After the sodium nitrate is fully adsorbed, add 2.14 mL of sodium nitrate and 140 mg of sodium nitrate. Ir mL -1 Ir ions are embedded in the interstitial spaces of Na ions using a chloroiridium acid solution, forming a natural spatial barrier. The mixture is then ultrasonically dispersed for 20 minutes, followed by stirring at room temperature for 2 hours to ensure homogeneity. After feeding, the mixture is milled in a planetary ball mill for 5 hours, and then ultrasonically dispersed for 30 minutes to ensure the Ir source is fully adsorbed onto the Nb₂O₅ support surface.
[0034] After uniform mixing, the above mixed solution was rotary evaporated in a 60℃ water bath to remove moisture, obtaining a brownish-yellow solid precursor. The dried solid precursor was ground to ensure uniform dispersion, then transferred to a corundum crucible and placed in a forced-air drying oven. It was heated to 450℃ at a heating rate of 5℃ / min in air and held for 180 min, followed by natural cooling to room temperature. The product after high-temperature oxidation was added to water and ultrasonically dispersed for 1 h. Then, it was dialyzed for 7 days using a dialysis bag, and thoroughly washed to remove impurities such as sodium and chloride ions. The dialyzed solution was rotary evaporated in a 60℃ water bath to remove moisture, and the solid was ground uniformly to obtain niobium pentoxide-supported sub-nanometer iridium oxide cluster material, denoted as IrO. x @Nb2O5.
[0035] In this embodiment, the obtained niobium pentoxide-supported sub-nanometer iridium oxide cluster material was characterized by X-ray diffraction, and the results are as follows: Figure 1 As shown, the sample exhibits characteristic diffraction peaks of Nb₂O₅, while the crystal diffraction peaks of IrO₂ are broad, indicating that the supported oxygen IrO₂ exists in an amorphous state, consistent with the structural characteristics of sub-nano clusters.
[0036] In this embodiment, the obtained niobium pentoxide-supported sub-nanometer iridium oxide cluster material was characterized by TEM and iridium oxide particle size analysis was performed. The results are as follows: Figure 2 As shown in the figure. It can be seen that the IrO in the obtained catalyst... x Nanoclusters are uniformly dispersed on the surface of the Nb₂O₅ support, and IrO x The average particle size is only 0.83 nm.
[0037] In this embodiment, the obtained niobium pentoxide-supported sub-nanometer iridium oxide cluster material was characterized by SEM, and the results are as follows: Figure 3 As shown, the Nb₂O₅ support exhibits a relatively uniform granular morphology, with sub-nanometer IrO₂... x The clusters were uniformly dispersed on the surface of the carrier without obvious agglomeration, indicating that the synthesis method used was beneficial to the uniform loading of the active components.
[0038] In this embodiment, elemental mapping analysis was performed on the obtained niobium pentoxide-supported sub-nanometer iridium oxide cluster material, and the results are as follows: Figure 4 As shown, the catalyst contains Nb, Ir, and O elements simultaneously, confirming the effective loading of Ir in the Nb₂O₅ support.
[0039] In this embodiment, the obtained niobium pentoxide-supported sub-nanometer iridium oxide cluster material was used as a catalyst as the anode (loading was 0.5 mg). Ir cm -2 Using Pt / C as the cathode (with a loading of 0.2 mg) pt cm -2 The membrane electrode assembly (MEA) was prepared by coating a Nafion 115 proton exchange membrane (PEM) as the electrolyte membrane. The catalyst slurry was uniformly sprayed onto the PTFE surface, and then hot-pressed at 130°C for 2 Ton for 3 minutes to completely transfer the catalyst onto the MEM to prepare the CCM. The anode gas diffusion layer used a platinum-plated titanium felt, and the cathode gas diffusion layer used a titanium felt composite carbon paper structure. The MEA was then prepared and assembled into a single-cell proton exchange membrane water electrolysis device.
[0040] The aforementioned proton exchange membrane electrolysis water single-cell device was tested at 60℃ and 80℃ to obtain its constant current polarization curves, as shown in the figure. Figure 5 As shown. It can be seen that the water electrolysis device using the niobium pentoxide-supported sub-nanometer iridium oxide clusters prepared in this invention as the anode catalyst operates at 2A. cm -2 At current densities, the required decomposition voltage is only 1.797V (60℃) and 1.715V (80℃), demonstrating excellent catalytic activity.
[0041] Furthermore, the aforementioned proton exchange membrane electrolysis water single-cell device, at 80°C and 2A... cm -2 Under these conditions, a constant current durability test was conducted, with ultrapure water (flow rate 10 mL) passed through the anode. min - ¹), the test lasted 1350 hours, and the results were as follows: Figure 6 As shown in the figure. It can be seen that the electrolysis device using the niobium pentoxide-supported sub-nanometer iridium oxide clusters as the anode catalyst operates at 2A. cm -2 At the current density, the decay rate over 1350 hours is only 17.54 μV. h -1 Its application performance is good.
[0042] Example 2 A large amount of niobium pentoxide support was pre-milled in a planetary ball mill for 40 min, and the resulting 200-mesh ultrafine support powder was obtained after sieving. The ultrafine support powder was then placed in a plasma reaction chamber, evacuated, and purged with an Ar / O2 mixed gas (volume ratio 10:1). The working pressure was adjusted to 20 Pa, and the radio frequency plasma was turned on. The mixture was treated at 120 °C for 5 min, cooled under the atmosphere, and removed to obtain the niobium pentoxide precursor. 0.2 g of the niobium pentoxide precursor was weighed and placed in a container, and 20 mL of isopropanol was added as a solvent. The mixture was ultrasonically dispersed for 30 min to form a support suspension.
[0043] First, add 5.0 g of sodium nitrate to the carrier suspension and sonicate for 20 min. After the sodium nitrate has been fully adsorbed, add 2.14 mL of sodium nitrate and 140 mg of sodium nitrate. Ir mL -1 The Ir ions were embedded in the interstitial spaces of the Na ions to form a natural spatial barrier. The mixture was then ultrasonically dispersed for 20 minutes, followed by stirring at room temperature for 2 hours to ensure homogeneity. After feeding, the mixture was ground in a planetary ball mill for 5 hours, and then ultrasonically dispersed for 30 minutes to ensure the Ir source was fully adsorbed onto the Nb₂O₅ support surface.
[0044] After uniform mixing, the mixed solution was rotary evaporated in a 60℃ water bath to remove moisture, yielding a brownish-yellow solid precursor. The dried solid precursor was ground to ensure uniform dispersion, then transferred to a corundum crucible and placed in a forced-air drying oven. It was heated to 450℃ at a heating rate of 5℃ / min in air and held for 180 min, followed by natural cooling to room temperature. The product after high-temperature oxidation was added to water and sonicated for 1 h, then dialyzed through a dialysis bag for 7 days, thoroughly washing to remove impurities such as sodium and chloride ions. The dialyzed solution was rotary evaporated in a 60℃ water bath to remove moisture, and the solid was ground uniformly to obtain niobium pentoxide-supported sub-nanometer iridium oxide cluster material, denoted as IrO. x @Nb2O5.
[0045] In this embodiment, the obtained niobium pentoxide-supported sub-nanometer iridium oxide clusters were subjected to membrane electrode polarization curves and durability tests, and the results were basically similar to those of the materials prepared in Example 1.
[0046] Example 3 A large amount of niobium pentoxide support was pre-milled in a planetary mill for 40 min, and then sieved to obtain 200-mesh ultrafine support powder. The obtained ultrafine support powder was then placed in a plasma reaction chamber, evacuated, and purged with an Ar / O2 mixed gas (volume ratio 10:1). The working pressure was adjusted to 20 Pa, and radio frequency plasma was activated. The mixture was treated at 120℃ for 5 min, cooled under the atmosphere, and then removed to obtain the niobium pentoxide precursor. 2.0 g of the niobium pentoxide precursor was weighed and placed in a container, and 100 mL of isopropanol and 100 mL of water were added as solvents. The mixture was ultrasonically dispersed for 30 min to form a support suspension. 50 g of sodium nitrate was first added to the support suspension, and the mixture was ultrasonically dispersed for 20 min. After the sodium nitrate was fully adsorbed, 21.40 mL of sodium nitrate and 140 mg of sodium nitrate were added. Ir mL -1 The Ir ions were embedded in the interstitial spaces of the Na ions to form a natural spatial barrier. The mixture was then ultrasonically dispersed for 20 minutes, followed by stirring at room temperature for 2 hours to ensure homogeneity. After feeding, the mixture was ground in a planetary ball mill for 5 hours, and then ultrasonically dispersed for 30 minutes to ensure the Ir source was fully adsorbed onto the Nb₂O₅ support surface.
[0047] After uniform mixing, the mixed solution was rotary evaporated in a 60℃ water bath to remove moisture, yielding a brownish-yellow solid precursor. The dried solid precursor was ground to ensure uniform dispersion, then transferred to a corundum crucible and placed in a forced-air drying oven. It was heated to 450℃ at a heating rate of 5℃ / min in air and held for 180 min, followed by natural cooling to room temperature. The product after high-temperature oxidation was added to water and sonicated for 1 h, then dialyzed through a dialysis bag for 7 days, thoroughly washing to remove impurities such as sodium and chloride ions. The dialyzed solution was rotary evaporated in a 60℃ water bath to remove moisture, and the solid was ground uniformly to obtain niobium pentoxide-supported sub-nanometer iridium oxide cluster material, denoted as IrO. x @Nb2O5.
[0048] In this embodiment, the prepared niobium pentoxide-supported sub-nanometer iridium oxide clusters were subjected to membrane electrode polarization curves and durability tests, and the results were similar to those of the catalyst prepared in Example 1.
[0049] Example 4 The preparation method of the catalyst material described in this embodiment is the same as that in Embodiment 1, except that the metal oxide support is selected as chromium dioxide (CrO2).
[0050] A large amount of CrO2 support was pre-milled in a planetary mill for 40 min, and then sieved to obtain 200-mesh ultrafine support powder. The obtained ultrafine support powder was then placed in a plasma reaction chamber, evacuated, and purged with an Ar / O2 mixed gas (volume ratio 10:1). The working pressure was adjusted to 20 Pa, and the radio frequency plasma was turned on. The mixture was treated at 120℃ for 5 min, cooled under the atmosphere, and then removed to obtain the CrO2 precursor. 0.2 g of the CrO2 precursor was weighed and placed in a container, and 10 mL of isopropanol and 10 mL of water were added as solvents. The mixture was ultrasonically dispersed for 30 min to form a support suspension. 5.0 g of sodium nitrate was first added to the support suspension, and the mixture was ultrasonically dispersed for 20 min. After the sodium nitrate was fully adsorbed, 2.14 mL of sodium nitrate and 140 mg of sodium nitrate were added. Ir mL -1Ir ions were embedded in the interstitial spaces of Na ions using a chloroiridium acid solution to form natural spatial barriers. The mixture was then ultrasonically dispersed for 20 min, followed by stirring at room temperature for 2 h to ensure homogeneity. After addition, the mixture was ground in a planetary ball mill for 5 h, then ultrasonically dispersed for 30 min to ensure sufficient adsorption of the Ir source onto the CrO2 support surface. After homogeneity, the solution was rotary evaporated in a 60°C water bath to remove moisture, yielding a brownish-green solid precursor. The dried solid precursor was ground to ensure uniform dispersion, then transferred to a corundum crucible and placed in a forced-air drying oven. It was heated to 450°C at a heating rate of 5°C / min and held for 180 min in air, followed by natural cooling to room temperature. The product after high-temperature oxidation was added to water and ultrasonically treated for 1 h, then dialyzed using a dialysis bag for 7 days, thoroughly washing to remove sodium, chloride, and other impurities. The dialyzed solution was rotary evaporated in a 60°C water bath to remove moisture, and the solid was ground uniformly to obtain chromium dioxide-supported sub-nanometer iridium oxide cluster material, denoted as IrO. x @CrO2.
[0051] In this embodiment, the prepared chromium dioxide-supported sub-nanometer iridium oxide clusters were subjected to membrane electrode polarization curves and durability tests, and the results were similar to those of the catalyst prepared in Example 1.
[0052] Example 5 The preparation method of the catalyst material described in this embodiment is the same as that in Embodiment 1, except that the metal oxide support is selected as tin dioxide (SnO2).
[0053] A large amount of SnO2 support was pre-milled in a planetary mill for 40 min, and then sieved to obtain 200-mesh ultrafine support powder. The obtained ultrafine support powder was then placed in a plasma reaction chamber, and after evacuating to a background pressure below 1 Pa, an Ar / O2 mixed gas (volume ratio 10:1) was introduced. The working pressure was adjusted to 20 Pa, and the radio frequency plasma was turned on. The mixture was treated at 120℃ for 5 min, cooled under the atmosphere, and then removed to obtain the SnO2 precursor. 0.2 g of the SnO2 precursor was weighed and placed in a container, and 10 mL of isopropanol and 10 mL of water were added as solvents. The mixture was ultrasonically dispersed for 30 min to form a support suspension. 5.0 g of sodium nitrate was first added to the support suspension, and the mixture was ultrasonically dispersed for 20 min. After the sodium nitrate was fully adsorbed, 2.14 mL of sodium nitrate and 140 mg of sodium nitrate were added. Ir mL -1Ir ions were embedded in the interstitial spaces of Na ions using a chloroiridium acid solution to form natural spatial barriers. The mixture was then ultrasonically dispersed for 20 min, followed by stirring at room temperature for 2 h to ensure homogeneity. After addition, the mixture was ground in a planetary ball mill for 5 h, then ultrasonically dispersed for 30 min to ensure sufficient adsorption of the Ir source onto the SnO2 support surface. After homogeneous mixing, the solution was rotary evaporated in a 60°C water bath to remove moisture, yielding a brownish-yellow solid precursor. The dried solid precursor was ground to ensure uniform dispersion, then transferred to a corundum crucible and placed in a forced-air drying oven. It was heated to 450°C at a heating rate of 5°C / min and held for 180 min in air, followed by natural cooling to room temperature. The product after high-temperature oxidation was added to water and ultrasonically treated for 1 h, then dialyzed using a dialysis bag for 7 days, thoroughly washing to remove sodium, chloride, and other impurities. The dialyzed solution was rotary evaporated in a 60°C water bath to remove moisture, and the solid was ground uniformly to obtain tin dioxide-supported sub-nanometer iridium oxide cluster material, denoted as IrO. x @SnO2.
[0054] In this embodiment, the prepared tin dioxide-supported sub-nanometer iridium oxide clusters were subjected to membrane electrode polarization curves and durability tests, and the results were similar to those of the catalyst prepared in Example 1.
[0055] Example 6 The preparation method of the catalyst material described in this embodiment is the same as that in Embodiment 1, except that the metal oxide support is zirconium dioxide (ZrO2).
[0056] A large amount of ZrO2 support was pre-milled in a planetary mill for 40 min, and then sieved to obtain 200-mesh ultrafine support powder. The obtained ultrafine support powder was then placed in a plasma reaction chamber, and after evacuating to a background pressure below 1 Pa, an Ar / O2 mixed gas (volume ratio 10:1) was introduced. The working pressure was adjusted to 20 Pa, and the radio frequency plasma was turned on. The mixture was treated at 120℃ for 5 min, cooled under the atmosphere, and then removed to obtain the ZrO2 precursor. 0.2 g of the ZrO2 precursor was weighed and placed in a container, and 10 mL of isopropanol and 10 mL of water were added as solvents. The mixture was ultrasonically dispersed for 30 min to form a support suspension. 5.0 g of sodium nitrate was first added to the support suspension, and the mixture was ultrasonically dispersed for 20 min. After the sodium nitrate was fully adsorbed, 2.14 mL of sodium nitrate and 140 mg of sodium nitrate were added. Ir mL -1Ir ions were embedded in the interstitial spaces of Na ions using a chloroiridium acid solution to form natural spatial barriers. The mixture was then ultrasonically dispersed for 20 min, followed by stirring at room temperature for 2 h to ensure homogeneity. After addition, the mixture was ground in a planetary ball mill for 5 h, then ultrasonically dispersed for 30 min to ensure sufficient adsorption of the Ir source onto the ZrO2 support surface. After homogeneous mixing, the solution was rotary evaporated in a 60°C water bath to remove moisture, yielding a brownish-yellow solid precursor. The dried solid precursor was ground to ensure uniform dispersion, then transferred to a corundum crucible and placed in a forced-air drying oven. It was heated to 450°C at a heating rate of 5°C / min and held for 180 min in air, followed by natural cooling to room temperature. The product after high-temperature oxidation was added to water and ultrasonically treated for 1 h, then dialyzed for 7 days using a dialysis bag, thoroughly washing to remove sodium, chloride, and other impurities. The dialyzed solution was rotary evaporated in a 60°C water bath to remove moisture, and the solid was ground uniformly to obtain the zirconium dioxide-supported sub-nanometer iridium oxide cluster material, denoted as IrO. x @ZrO2.
[0057] In this embodiment, the prepared zirconium dioxide-supported sub-nanometer iridium oxide clusters were subjected to membrane electrode polarization curves and durability tests, and the results were similar to those of the catalyst prepared in Example 1.
[0058] Example 7 The preparation method of the catalyst material described in this embodiment is the same as that in Example 1, except that 0.6g of hexadecyltrimethylbromoalkane is added in the feeding stage of step (2).
[0059] A large amount of niobium pentoxide support was pre-milled in a planetary ball mill for 40 min, and the resulting 200-mesh ultrafine support powder was obtained after sieving. The ultrafine support powder was then placed in a plasma reaction chamber, evacuated, and purged with an Ar / O2 mixed gas (volume ratio 10:1). The working pressure was adjusted to 20 Pa, and the radio frequency plasma was activated. The mixture was treated at 120℃ for 5 min, cooled under the atmosphere, and removed to obtain the niobium pentoxide precursor. 0.2 g of the niobium pentoxide precursor and 0.6 g of hexadecyltrimethylbromoalkane support were weighed and placed in a container. 10 mL of isopropanol and 10 mL of water were added as solvents, and the mixture was ultrasonically dispersed for 30 min to form a support suspension. 5.0 g of sodium nitrate was first added to the support suspension, and the mixture was ultrasonically dispersed for 20 min. After the sodium nitrate was fully adsorbed, 2.14 mL of sodium nitrate and 140 mg of sodium nitrate were added. Ir mL -1A chloroiridium acid solution was used to embed Ir ions into the interstices of Na ions, forming a natural spatial barrier. The mixture was then ultrasonically dispersed for 20 min, followed by stirring at room temperature for 2 h to ensure homogeneity. After addition, the mixture was ground in a planetary ball mill for 5 h, then ultrasonically dispersed for 30 min to ensure sufficient adsorption of the Ir source onto the Nb₂O₅ support surface. After homogeneous mixing, the solution was rotary evaporated in a 60°C water bath to remove moisture, yielding a brownish-yellow solid precursor. The dried solid precursor was ground to ensure uniform dispersion, then transferred to a corundum crucible and placed in a forced-air drying oven. It was heated to 450°C at a heating rate of 5°C / min and held at this temperature for 180 min, followed by natural cooling to room temperature. The product after high-temperature oxidation was added to water and ultrasonically treated for 1 h, then dialyzed using a dialysis bag for 7 days, with thorough washing to remove impurities such as sodium and chloride ions. The dialyzed solution was evaporated to remove water under a 60°C water bath. The solid was then ground to obtain niobium pentoxide-supported sub-nanometer iridium oxide clusters, denoted as IrO. x @Nb2O5.
[0060] In this embodiment, niobium pentoxide-supported sub-nanometer iridium oxide clusters were prepared as a catalyst and used as the anode (0.5 mg). Ir cm -2 Using Pt / C as the cathode (with a loading of 0.2 mg) pt cm -2 The membrane electrode was coated and assembled into a proton exchange membrane water electrolysis device. Constant current polarization curves were obtained by testing at 60℃ and 80℃, and the results are attached. Figure 7 The results showed that, when a current density of 2A was provided... cm -2 The required decomposition voltages are 1.837V (60℃) and 1.717V (80℃), respectively, which are 40mV (60℃) and 2mV (80℃) higher than the scheme in Example 1, respectively.
[0061] In this embodiment, the prepared supported sub-nanometer iridium oxide clusters were subjected to durability testing, and the results were similar to those of the catalyst prepared in Example 1.
[0062] It is evident that in the feed system, the addition of CTAB can independently generate uniformly sized iridium oxide nanoparticles through micellar confinement, which then adhere to the surface of the niobium pentoxide support, enabling precise control of Ir grain size. While the competitive occupation of active sites by CTAB cations slightly affects the strong binding interface between iridium and niobium oxide, causing slight fluctuations in the operating voltage, the impact on catalytic stability is minimal.
[0063] Comparative Example 1 The difference between this comparative example and Example 1 is that ball milling and Ar / O2 plasma cryogenic treatment are not performed during the precursor pretreatment process.
[0064] Weigh 0.2 g of niobium pentoxide support and place it in a container. Add 10 mL of isopropanol and 10 mL of water as a mixed solvent. Add 2.14 mL of niobium pentoxide support and 140 mg of water. Ir mL -1 A chloroiridium acid solution was ultrasonically dispersed for 30 min and stirred at room temperature for 2 h to form a carrier suspension. 5.0 g of sodium nitrate was added to the carrier suspension, and the mixture was ultrasonically dispersed for 20 min. After the sodium nitrate was fully adsorbed, Ir ions were embedded in the interstitial spaces of Na ions to form natural spatial barriers, allowing the Ir source to be fully adsorbed on the surface of the Nb₂O₅ carrier.
[0065] After uniform mixing, the mixed solution was rotary evaporated in a 60℃ water bath to remove moisture, yielding a brownish-yellow solid precursor. The dried solid precursor was ground to ensure uniform dispersion, then transferred to a corundum crucible and placed in a forced-air drying oven. It was heated to 450℃ at a heating rate of 5℃ / min in air and held for 180 min, followed by natural cooling to room temperature. The product after high-temperature oxidation was added to water and sonicated for 1 h, then dialyzed through a dialysis bag for 7 days, thoroughly washing to remove impurities such as sodium and chloride ions. The dialyzed solution was rotary evaporated in a 60℃ water bath to remove moisture, and the solid was ground uniformly to obtain niobium pentoxide-supported sub-nanometer iridium oxide cluster material, denoted as IrO. x @Nb2O5.
[0066] The niobium pentoxide-supported sub-nanometer iridium oxide cluster material prepared in this comparative example was used as a catalyst and anode (0.5 mg). Ir cm -2 Using Pt / C as the cathode (with a loading of 0.2 mg) pt cm -2 The membrane electrode was coated and assembled into a proton exchange membrane water electrolysis device (same as in Example 1). Constant current polarization curves were obtained by testing at 60℃ and 80℃, and the results are attached. Figure 8 .
[0067] The results showed that it was effective at a current density of 2A. cm -2 The required decomposition voltages are 1.830V (60℃) and 1.736V (80℃), respectively, which are 33mV (60℃) and 21mV (80℃) higher than the scheme in Example 1, respectively.
[0068] Comparative Example 2 The preparation method of the catalyst material described in this comparative example is the same as that in Example 1, except that in the washing process of step (3), 0.5M nitric acid solution and ultrapure water are used for filtration, and dialysis is not performed.
[0069] A large amount of niobium pentoxide support was pre-milled in a planetary ball mill for 40 min, and the resulting 200-mesh ultrafine support powder was obtained after sieving. The ultrafine support powder was then placed in a plasma reaction chamber, evacuated, and purged with an Ar / O2 mixed gas (volume ratio 10:1). The working pressure was adjusted to 20 Pa, and the radio frequency plasma was activated. The mixture was treated at 120 °C for 5 min, cooled under the atmosphere, and removed to obtain the niobium pentoxide precursor. 0.2 g of the niobium pentoxide precursor was weighed and placed in a container, and 10 mL of isopropanol and 10 mL of water were added as a mixed solvent. The mixture was ultrasonically dispersed for 30 min to form a support suspension.
[0070] First, add 5.0 g of sodium nitrate to the carrier suspension and sonicate for 20 min. After the sodium nitrate has been fully adsorbed, add 2.14 mL of sodium nitrate and 140 mg of sodium nitrate. Ir mL -1 The Ir ions were embedded in the interstitial spaces of the Na ions to form a natural spatial barrier. The mixture was then ultrasonically dispersed for 20 minutes, followed by stirring at room temperature for 2 hours to ensure homogeneity. After feeding, the mixture was ground in a planetary ball mill for 5 hours, and then ultrasonically dispersed for 30 minutes to ensure the Ir source was fully adsorbed onto the Nb₂O₅ support surface.
[0071] After uniform mixing, the mixture was rotary evaporated in a 60°C water bath to remove moisture, yielding a brownish-yellow solid precursor. The dried solid precursor was ground to ensure uniform dispersion, then transferred to a corundum crucible and placed in a forced-air drying oven. It was heated to 450°C at a heating rate of 5°C / min in air and held for 180 min, followed by natural cooling to room temperature. The product after high-temperature oxidation was added to water and sonicated for 1 h. It was then filtered and washed with 0.5M nitric acid solution for 1 h to remove impurities such as sodium and chloride ions. 2 L of ultrapure water was added and filtered to neutralize the solution. The resulting filter cake was dried overnight in a 60°C oven. After uniform grinding, niobium pentoxide-supported sub-nanometer iridium oxide clusters, denoted as IrO, were obtained. x @Nb2O5.
[0072] The niobium pentoxide-supported sub-nanometer iridium oxide cluster material prepared in this comparative example was used as a catalyst and anode (0.5 mg). Ir cm -2 Using Pt / C as the cathode (with a loading of 0.2 mg) pt cm -2The membrane electrode was coated and assembled into a proton exchange membrane water electrolysis device (same as in Example 1). Constant current polarization curves were obtained by testing at 60℃ and 80℃, and the results are attached. Figure 9 .
[0073] The results showed that it was effective at a current density of 2A. cm -2 The required decomposition voltages are 1.800V (60°C) and 1.740V (80°C), respectively. These values are 3mV (60°C) and 25mV (80°C) higher than those in Example 1, respectively.
[0074] In summary, the supported sub-nanometer iridium oxide cluster material described in this invention is used as an anode catalyst for proton exchange membrane water electrolysis, exhibiting both excellent catalytic activity and electrochemical stability. It not only operates stably in applications but also has an extremely low decay rate, demonstrating excellent application performance.
[0075] The embodiments of the present invention have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.
Claims
1. A supported sub-nanometer iridium oxide cluster material, characterized in that, The material comprises a carrier and supported active clusters; wherein, The active clusters include sub-nanometer iridium oxide clusters with a particle size of <1 nm; The carrier comprises metal oxides.
2. The supported sub-nanometer iridium oxide cluster material according to claim 1, characterized in that, The active clusters are loaded at a rate of 30-70 wt% based on the carrier.
3. The supported sub-nanometer iridium oxide cluster material according to claim 1 or 2, characterized in that: The iridium oxide cluster includes Ir x O y Where x=1, y=1.5-2.2; and / or, The metal oxide includes one or a mixture of several of niobium pentoxide, chromium dioxide, titanium dioxide, zirconium dioxide, or tin dioxide.
4. A method for preparing a supported sub-nanometer iridium oxide cluster material as described in any one of claims 1-3, characterized in that, Includes the following steps: (1) Take a selected amount of the metal oxide for surface pretreatment to obtain the desired carrier, and add a dispersing solvent to mix and form a carrier suspension; (2) Continue to add alkali metal nitrate and Ir source material to the carrier suspension, mix and disperse to obtain a mixed liquid; (3) The mixture is evaporated to dryness to obtain a precursor solid; the precursor solid is then subjected to high-temperature calcination to obtain the desired supported sub-nanometer iridium oxide cluster material.
5. The method for preparing the supported sub-nanometer iridium oxide cluster material according to claim 4, characterized in that, In step (1), the pretreatment step includes grinding and sieving the metal oxide to obtain carrier powder, and performing Ar / O2 plasma low-temperature treatment and / or acid washing on the carrier powder. The grinding steps include a step of coarse grinding with an agate mortar for 5-30 minutes; and / or a step of ball milling with a planetary ball mill at a speed of 300-600 rpm for 0.5-6 hours. The sieving step yields a carrier powder of 200-400 mesh; and / or, In the plasma cryogenic treatment step, the volume ratio of Ar gas to O2 is (5-20):1; and / or, The duration of the plasma cryogenic treatment step is 5-60 minutes; and / or, The temperature of the plasma cryogenic treatment step is 50-300℃; and / or, The acid used in the pickling step includes at least one of nitric acid, hydrochloric acid, and sulfuric acid; and / or, The acid concentration used in the pickling step is 0.1-2 mol / L; and / or, The pickling temperature in the pickling step is 25-80℃; and / or, The pickling time for the pickling step is 0.5-6 hours; and / or, The dispersing solvent includes one or more of the following: an alcohol solvent or a mixture of several solvents, such as water; and / or, The carrier suspension has a carrier solids content of 0.01-0.05 wt%.
6. The method for preparing the supported sub-nanometer iridium oxide cluster material according to claim 4 or 5, characterized in that, In step (2): The alkali metal nitrates include one or a mixture of several of sodium nitrate, potassium nitrate, zinc nitrate, etc.; and / or, The Ir source material includes one or a mixture of several of iridium chloroiridic acid, iridium trichloride, potassium iridium chloroiridate, or iridium acetylacetonate; and / or, The amount of the alkali metal nitrate added is 1-15 times the mass of the carrier; and / or, The mass ratio of the carrier to the Ir source material is 10:1 to 1:10; and / or, The dispersion process includes one or more of the following methods: ultrasonication, stirring, or ball milling; and / or, It also includes the step of adding a surfactant to the mixture, preferably, the surfactant comprising one or a mixture of several of hexadecyltrimethylbromoalkane, polyvinylpyrrolidone, and sodium dodecyl sulfate.
7. The method for preparing the supported sub-nanometer iridium oxide cluster material according to any one of claims 4-6, characterized in that, In step (3): The temperature of the evaporation step is 40-65℃; and / or, The evaporation step takes 20-150 minutes; and / or, The atmosphere for the high-temperature calcination step is an oxygen-containing atmosphere, preferably an air atmosphere; and / or, The temperature of the high-temperature calcination step is 300-550℃; and / or, The heating rate of the high-temperature calcination step is 5-10℃ / min; and / or, The high-temperature calcination step takes 30-180 minutes; and / or, The method also includes the steps of collecting the high-temperature calcination products for dispersion, washing, separation and drying.
8. The use of the supported sub-nanometer iridium oxide cluster material as described in any one of claims 1-3 for preparing a proton exchange membrane water electrolysis hydrogen production anode catalyst.
9. A proton exchange membrane electrolysis anode catalyst for hydrogen production, characterized in that, Includes the supported sub-nanometer iridium oxide cluster material as described in any one of claims 1-3.
10. A process for producing hydrogen by proton exchange membrane electrolysis of water, characterized in that, The step includes anodic catalysis using the proton exchange membrane electrolysis anode catalyst for hydrogen production as described in claim 9.